Increasing trends in obesity prevalence from 2013 to 2019 and associated factors in Brazil - Arthur Pate de Souza Ferreira; Célia Landmann Szwarcwald; Giseli Nogueira Damacena; Paulo Roberto Borges de Souza Júnior
ABSTRACT: Objective: To investigate the variation of anthropometric indicators from 2013 to 2019 and the factors associated with obesity in Brazil, using information from the National Health Survey. Methods: Cross-sectional study with cluster sampling and simple random sampling in the three stages. Measurements of weight and height among participants in 2013 (n=59,592) and in 2019 (n=6,672) were used. Differences in obesity prevalence were tested by Student's t test for independent samples. To identify the sociodemographic factors and health problems associated with obesity, we used Poisson regression models with robust variance and crude and age-adjusted prevalence ratios to test the associations. Results: From 2013 to 2019, prevalence of obesity increased significantly, from 20.8 to 25.9%. Among men, the greatest increases were found in the 40-59 age group (9.1%) and in the median income category (8.3%). Among women, the greatest rises were found among those with low education (8.7%) and non-white ones (6.0%). For both males and females, factors associated with obesity were age, to live with a partner, level of instruction directly associated among men, and inversely associated among women. In 2019, for males, the crude and adjusted prevalence ratios were significant for high cholesterol, high blood pressure and at least one chronic non-communicable disease and, for females, for poor self-rated health, high blood pressure, diabetes, and at least one chronic non-communicable. Conclusion: It is necessary to implement intersectoral policies to promote changes in eating habits and encourage the practice of physical activity, taking into account economic, social, cultural, and environmental aspects.